Reproducibility measures and their effect on diet–cancer associations in the Boyd Orr cohort. Issue 5 (13th April 2007) - Frobisher, Clare; Tilling, Kate; Emmett, Pauline M; Maynard, Maria; Ness, Andrew R; Davey Smith, George; Frankel, Stephen J; Gunnell, David J
Abstract : Objectives: To quantify measurement error in the estimation of family diet intakes using 7-day household food inventories and to investigate the effect of measurement-error adjustment on diet–disease associations. Design and setting: Historical cohort study in 16 districts in England and Scotland, between 1937 and 1939. Subjects: 4999 children from 1352 families in the Carnegie Survey of Diet and Health. 86.6% of these children were traced as adults and form the Boyd Orr cohort. The reproducibility analysis was based on 195 families with two assessments of family diet recorded 3–15 months apart. Methods: Intraclass correlation coefficients (ICCs) were calculated for a variety of nutrients and food groups. Diet–cancer associations reported previously in the Boyd Orr cohort were reassessed using two methods: (a) the ICC and (b) the regression calibration. Main results: The ICCs for the dietary intakes ranged from 0.44 (β carotene) to 0.85 (milk and milk products). The crude fully adjusted hazard ratio (HR) for cancer mortality per 1 MJ/day increase in energy intake was 1.15 (95% CI 1.06 to 1.24). After adjustment using the ICC for energy (0.80) the HR (95% CI) increased to 1.19 (1.08 to 1.31), and the estimate from regression calibration was 1.14 (0.98 to 1.32). The crude fully adjusted odds ratio (OR) for cancer incidence per 40 g/day increase in fruit intake was 0.84 (95% CI 0.73 to 0.97). After adjustment using the fruit ICC (0.78) it became 0.81 (0.67 to 0.96) and the OR derived from regression calibration was 0.81 (0.59 to 1.10). Conclusions: The diet–disease relationships for the dietary intakes with low measurement error were robust to adjustment for measurement error.